PUBLICATION REQUIREMENTS - Arias Castilla, Carmen Aura (Horizontes pedagógicos, 2016)
This Journal is a scientific publication prepared by the Faculty of Education at the Corporación Universitaria Iberoamericana. This publication is based on dialogic academic perspective that tries to open spaces for reflection and discussion about educative knowledge and experiences which understand the complexity and the extent of the field. This publication also attempts to offer answers to the need for continue professional development for educators in our society through the promotion of the research activities in the fields of education and pedagogy